2004
DOI: 10.1016/j.cub.2004.09.081
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Regulating SHORT-ROOT Intercellular Movement

Abstract: Signaling centers within developing organs regulate morphogenesis in both plants and animals. The putative transcription factor SHORT-ROOT (SHR) is an organizing signal regulating the division of specific stem cells in the Arabidopsis root. Comparison of gene transcription with protein localization indicates that SHR moves in a highly specific manner from the cells of the stele in which it is synthesized outward. Here, we provide evidence that SHR intercellular trafficking is both regulated and targeted. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
191
2
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(207 citation statements)
references
References 25 publications
(1 reference statement)
10
191
2
4
Order By: Relevance
“…As JKD and BIB form nuclear complexes with both SCR and SHR, it is plausible that BIRD proteins and SCR cooperate in the endodermis to prevent movement of SHR beyond one cell layer, in agreement with previously described data on the role of SCR (Gallagher et al, 2004;Cui et al, 2007;Koizumi et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…As JKD and BIB form nuclear complexes with both SCR and SHR, it is plausible that BIRD proteins and SCR cooperate in the endodermis to prevent movement of SHR beyond one cell layer, in agreement with previously described data on the role of SCR (Gallagher et al, 2004;Cui et al, 2007;Koizumi et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Intercellular signaling through mobile transcriptional regulators has been shown to be essential for plant growth and development (Lucas et al, 1995;Nakajima et al, 2001;Kim et al, 2003;Kurata et al, 2005;Gallagher and Benfey, 2009). In the Arabidopsis thaliana root meristem, the cell fate determinant SHORT-ROOT (SHR) is produced in the stele and moves one cell layer outward to instruct ground tissue development Nakajima et al, 2001;Sena et al, 2004;Gallagher et al, 2004;Gallagher and Benfey, 2009). After movement from the stele, SHR binds to its target SCR (SCARECROW) and promotes the asymmetric cell division (ACD) of the cortex-endodermis initial/daughter (CEI/CEID) as a bipartite SCR-SHR complex to generate the ground tissue (GT) consisting of two layers: cortex and endodermis (Di Laurenzio et al, 1996;Helariutta et al, 2000;Cui et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SHR pathway has been characterized primarily in Arabidopsis, where a single gene encodes a mobile protein that moves outward from its expression domain in the vasculature to specify cell fate in surrounding cell layers Nakajima et al, 2001;Gallagher et al, 2004;Levesque et al, 2006;Cui et al, 2007). Phylogenetic analysis revealed that the presence of a single SHR gene is typical of eudicot genomes, except where within-species genome duplications have occurred (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SHR is transcribed in the vascular tissue and the pericycle, collectively known as the stele. SHR protein, which localizes to the cytoplasm and the nucleus in the stele, is able to move from the cytoplasm of the stele cells to the adjacent SCRexpressing layer (Nakajima et al, 2001;Gallagher et al, 2004), including stem cells of the cortex/endodermis, their daughter cells, the endodermis, and the quiescent center. SHR protein becomes exclusively localized to the nucleus in cells of the SCR-expressing layer, where SHR directly up-regulates SCR to limit its own movement via SCR-dependent nuclear sequestration, thereby preventing its further movement into the cortex and maintaining its levels in the endodermis (Cui et al, 2007;Koizumi et al, 2012a).…”
mentioning
confidence: 99%